Variation of Serum Zinc Concentrations Among Kala-Azar Endemic and Nonendemic Population in Bangladesh - Basu, Kamalesh Chandra; Hoque, Mohammad Mahfuzul; Datta, Ponkaj Kanti; Samsuzzaman, Sheikh Mohammad; Hasan, Mohammad Jahidul; Rahman, Muhammad Faizur; Khan, Mohammed Masudul Hassan; Saifullah, Md; Kamal, Mohammad Mostafa; Hossain, Mohammad Zaid; et al. (Journal of Dhaka Medical College, 2023)
Background & objectives: Visceral Leishmaniasis (VL) or Kala-azar is a deadly disease putting 350 million people from 88 countries at risk. In Bangladesh, 45 districts are endemic. Zinc is an essential trace element and its relevance for proper functioning of the entire immune system is already well documented. Though low serum zinc levels have been reported in many parasitic diseases, limited information is available regarding zinc status in human leishmaniasis. This study was conducted to evaluate the zinc level in endemic and non-endemic population of kalaazar. Methods: This cross-sectional study was conducted to assess the serum zinc concentrations in kala-azar endemic and non- endemic population of 06 to 60 years of age range during the period of July 2014 to June 2015.Venous blood was collected from 92 subjects to estimate serum zinc concentrations. Results: Mean Serum zinc levels were found 63.66 microgm/dl in kala-azar patients of endemic area, 69.44 microgm/dl in kala-azar endemic populations and77.34 microgm/dl in non-endemic populations. Conclusion: The average serum zinc concentrations is lower in populations of kala-azar endemic zone compared to populations from kala-azar nonendemic zone. It was also found that kala-azar patient had lower zinc concentrations compared to non-kala-azar patients. There may have potential association of low zinc level and occurrence of kala-azar. J Dhaka Med Coll. 2021; 29(1): 111-117